Implementasi Pembelajaran Tahfidz Al - Qur’an Melalui Metode Talaqi - Nur Aisyah; Lu’luil Maknun (Program Studi PGMI IAINU Kebeumen, 2022)
One of the madrasahs ibtidaiyah schools aimed at memorizing the Al-Qur'an is at MIS AL-MUJAHIDAH. Graduates of this school can memorize Juz 29 and 30. In teaching Tahfidz here we use the Muraja'ah method so that students' memory develops and is developed especially in relation to recitation and chanting. The aim is to improve children's abilities by applying the talaqqi method, namely depositing direct memorization and the talaqqi method, namely repeating memorization. As a result of this study, children in grades 1 to 6 at MIS AL-MUJAHIDAH experienced an increase in their ability to memorize the Koran so that they were able to achieve their memorization goals. Based on the results of this study, it can be concluded that the application of the Talaqi method is effective in increasing the ability to memorize the Qur'an in grades 1 to 6. The best tafiz juz 30 and juz 29 will be held.